Notes on the genus Macroteratura Gorochov, 1993 (Tettigoniidae: Meconematinae: Meconematini) with description of one new species from China - Chen, Lixuan; Cui, Peng; Zhuo, Zhao; Chang, Yanlin (Zootaxa, 2020)
The paper deals with 7 species of the genus Macroteratura from China and provides information on examined specimens, of which one new species Macroteratura (Macroteratura) inospina Chen, Cui & Chang sp. nov. is described and illustrated with characteristic photographs of four known species from China.